Consenso sobre alimentación complementaria de la Sociedad Latinoamericana de Gastroenterología, Hepatología y Nutrición Pediátrica: COCO 2023 (2023)
Abstract Complementary feeding (CF) is defined as infant feeding that complements breastfeeding or, alternatively, breastfeeding with a breast milk substitute, and is a process that goes beyond simply providing guidance on what and how to introduce foods. The information provided by health professionals should be up-to-date and evidence-based. There are different guidelines or position papers at the international level, which, although most of the recommendations may be applicable, there are some others that require regionalization or adaptation to the conditions and reality of each area. The Nutrition working group of the Latin American Society of Pediatric Gastroenterology, Hepatology and Nutrition convened a group of experts, representatives from each of the countries that make up the society, with the objective of developing a consensus on CA, incorporating, when possible, local information that adapts to the reality of the region. The purpose of this document is to show the results of this work. Through Delphi methodology, a total of 34 statements or statements regarding relevant aspects of CA were evaluated, discussed and voted upon.